Climate Change, Water Security and Water-Energy-Food-Ecosystems (WEFE) Nexus Approaches - Part of a post-graduate course - Pandey, Vishnu Prasad; Rai, Rajesh Kumar; Koirala, Sanju; Bajracharya, Tri Ratna; Pokharel, Bharat Kumar; Onta, Nisha; Kattel, Rishi Ram; Dangol, Sabin; Khadka, Manohara; Elias, Marlene (2024)
Sustainable and integrated management of water, energy, food, and ecosystems requires a coordinated and cross-sectoral approach to manage trade-offs and maximize synergies among these deeply interconnected resources. This line of thinking and action is called the water-energy-food-ecosystem (WEFE) nexus approach. This academic course provides an overview of WEFE nexus concepts, issues, and approaches to develop the capacities of graduate students studying in any WEFE or WEFE-adjacent sector. The aim is to prepare future leaders in this area to foster the integrated, equitable, and sustainable management of WEFE resources. This course was co-developed under the umbrella of the CGIAR Initiative on NEXUS Gains by the Center for Water Resources Studies (CWRS), Institute of Engineering, Tribhuvan University, in partnership with the Alliance of Bioversity International and CIAT, and the International Water Management Institute (IWMI). It includes theory as well as practical applications and interactive elements.